Effect of proprioceptive neuromuscular facilitation versus Muscle energy technique in improving muscle Function in delayed onset muscle soreness In recreational players - ANAND KALAISELVAN,; KAMALAKANNAN.M,; SOWMYA.M.V, (International Journal of Pharma and Bio Sciences, 2017)
Delayed onset muscle soreness (DOMS) is a familiar experience for the elite or novice athlete. Symptoms can range from muscle tenderness to debilitating pain. The aim of the study is to analyze, the effect of Proprioceptive Neuromuscular Facilitatory technique (PNF) in comparison to Muscle Energy Technique (METs) in improving muscle function in delayed onset of muscle soreness (DOMS).Group A (PNF) n = 20, Group B (MET) n = 20, Group C (control) n = 20. Group A (PNF), Group B (METs) and Group C (control). All subjects were induced DOMS on their elbow flexors. The outcome measures MIVC, Pain and ROM were evaluated at baseline, 24, 48, 72 and 96 hours. One way ANOVA analysis revealed significant differences (p < 0.01) between baseline and 96 hours, as well as between 24, 48 and 72 hours, in the parameter of MIVC, Pain and ROM. Statistically significant difference (p < 0.01) was shown for MIVC and ROM, for Pain statistical significant (p > 0.05) was not found between the groups. In the present study METs (Group B) was found to be effective in improving the ROM and MIVC then PNF group (Group A). Whereas for pain outcome measure no significant difference were found between the experimental groups.